Ritz‐type surface homogenization: from atomistic to continuum surface models of copper despite imperfect bulk models. Issue 1 (25th January 2021) - Kurzeja, Patrick; Sievers, Christian; Brendel, Lothar; Mosler, Jörn
Abstract: Surfaces possess mechanical features on smaller scales that stand out against bulk phases, e.g., scaling of stiffness, curvature‐dependence, surfactant control and anchoring‐induced anisotropy. Continuum properties for the respective scales are often derived from ab initio simulations. This scale‐bridging however bears conceptual challenges and we highlight three aspects for the example of pure copper. First, free surface atoms relax and alter the boundary region in terms of interatomistic distances and resulting initital stresses. Second, eliminating the influence of finite thickness on the two‐dimensional continuum surface can be achieved by different averages or limit definitions, not all being physically consistent. Third, the continuum model of the surface is usually coupled to a continuum model of the bulk, which causes an approximation error itself. However, the bulk phase can not be eliminated direclty from the examination and simple averaging may even mask the aforementioned influences on the surface mechanics. A thermodynamically sound parameter identification across the scales is hence required. We present a Ritz‐type modeling approach for surfaces that ensures energy equivalence between atmostic and continuum simulations. The influences of relaxation, finite thickness and bulk approximation are identified by a mismatch in the energy contributions and accounted for by using appropriate homogenization limits.